Effects of melitten on isolated rat atrium - You Yu-Hong; Huang Zi-Qiang; Li Chang-Chun (Acta Pharmacologica Sinica; Vol 18, No 1 (January 1997): Acta Pharmacologica Sinica, 2016)
AIM :To8tudYtheefectsofmeliten(Md)onrat heart. METHODS: The isolated rat atria were adopted. Before and after giving M el, t}le heart rate,contraction ofatrium,post-restomataretion and staircase were m easured. RESULTS: Verapamil(V日 ) 0.1 ~tmol·L-1 was found to inhibit heart rate in the right atria of rats increased by M el20.0 mg·L~ . Inldtatriaofrats,the D0s£-rest o~ntracfon wa3 jnKbited na d typical positive staircase was markedly at tenuated by Md 2.5 m g ‘L~ . Md possessed negative inotropie elfecur on both t}le left na d right atria of rats. CONCLUSION: Md posesed negative inotropie and positive chronotropicactionson rat heart.